2015
DOI: 10.5267/j.msl.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of foreign direct investment in ASEAN: A panel approach

Abstract: This paper analyzes the factors of FDI inflows in ASEAN countries over the period 1991 to 2009. The results indicate that the market size, trade openness, quality infrastructure, human capital, labor productivity are the main factors that have positive impacts on FDI inflows. Additionally, exchange rate policy, real interest rate, political risk and corruption also affect FDI inflows. Surprisingly, the cheap labor does not help to attract FDI to the region, because foreign investors are particularly interested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
(39 reference statements)
3
22
0
1
Order By: Relevance
“…Many studies have been conducted on the relationship between capital flight and macroeconomic variables. Studies such as those by Brada (2011) and Hoa and Lin (2016) found a negative relationship between capital flight and macroeconomic variables, while Aderoju (2017), Saheed and Ayodeji (2012), and Uguru et al, (2014) found a positive relationship. Although most of the reviewed studies focused on the impact of capital flight on economic growth, the effects of capital flight on economic development have not been considered.…”
Section: Introductionmentioning
confidence: 96%
“…Many studies have been conducted on the relationship between capital flight and macroeconomic variables. Studies such as those by Brada (2011) and Hoa and Lin (2016) found a negative relationship between capital flight and macroeconomic variables, while Aderoju (2017), Saheed and Ayodeji (2012), and Uguru et al, (2014) found a positive relationship. Although most of the reviewed studies focused on the impact of capital flight on economic growth, the effects of capital flight on economic development have not been considered.…”
Section: Introductionmentioning
confidence: 96%
“…Trade openness (XM) means that trade barrier has been relaxed by the host country and it is an opportunity for investors to fully utilized the comparative advantage. Studies done by [9] and [10] found a significant positive impact of trade openness and GDP.…”
Section: Literature Reviewsmentioning
confidence: 91%
“…As mentioned in [1] factors influence GDP in ASEAN countries was FDI (proxy for investment inflows), labour productivity, trade openness, inflation rate (proxy for cost of production) and population growth (proxy for population density). GDP reflects the economic conditions and it gives positive impact to FDI as it reflects potential of the host country as validated by [9]. .…”
Section: Methodsmentioning
confidence: 99%
“…The available literatures are indeterminate to disclose the relationship between FDI inflows and labour productivity. The study of Hoang and Bui (2015), Peluffo (2014), Axarloglou (2004), Conyon et al (2002), Woodward (1992) and Cushman (1987) found a positive relationship between labour productivity and FDI inflows. On the other hand, the study of Boghean and State (2015) and Mebratie and Bedi (2013) revealed absence of relationship between labour productivity and FDI inflows, while Thiam Hee Ng (2006) found a positive weak relationship between these variables.…”
Section: Literature Reviewmentioning
confidence: 93%